Michael Field : Decadent Moderns - Parejo Vadillo, Ana, 1969-; Parker, Sarah, 1985- (Book collections on Project MUSE., 2019)
"In the last twenty years, Michael Field has emerged as one of the most fascinating poets of the Victorian era. Through their collaborative partnership as "Michael Field," Katharine Bradley and Edith Cooper engaged in the aesthetic and decadent movements of the fin de siecle, while their poetry and verse drama articulate ideas associated with the New Woman and boldly express queer and lesbian desire. Michael Field: Decadent Moderns extends the focus on these key literary and cultural contexts by emphasizing their continuing significance within twentieth-century literary modernism. Through a series of interdisciplinary essays, this book addresses Michael Field's energetic engagements with a range of topics including ecology, perfume, tourism, art history, sculpture, formalism, classics, and book history. In doing so, Michael Field: Decadent Moderns highlights the modernity, radicalism, and relevance of their work, both within the nineteenth and twentieth centuries as well as in our own cultural moment"--